2016
DOI: 10.1016/j.crpv.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

An interesting rock from Krapina

Abstract: a b s t r a c tSymbolic items are seldom associated with Neandertals and, when they are, many paleoanthropologists consider them to be Neandertal imitations from modern Homo sapiens. At the Croatian site of Krapina dated to MIS 5e or about 130,000 years ago, among many items, a split limestone rock was excavated by Dragutin Gorjanović-Kramberger between 1899-1905. This brownish rock reveals many dark dendritic forms in cross-and longitudinal section. Of more than 1000 lithic items at Krapina, none resemble thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…8 Moreover, recent (and not so recent) discoveries have shown that material cultures and behaviors previously solely associated with modern humans seem to have been present in some Neandertal populations. 13,[18][19][20][21][22][23][24] These data suggest that previous hypothesis that separated the populations into "modern" vs "archaic" no longer work.…”
Section: Patterns Of Bias Set By Preexisting Expectations and Assumptmentioning
confidence: 78%
See 1 more Smart Citation
“…8 Moreover, recent (and not so recent) discoveries have shown that material cultures and behaviors previously solely associated with modern humans seem to have been present in some Neandertal populations. 13,[18][19][20][21][22][23][24] These data suggest that previous hypothesis that separated the populations into "modern" vs "archaic" no longer work.…”
Section: Patterns Of Bias Set By Preexisting Expectations and Assumptmentioning
confidence: 78%
“…sapiens were no less complete versions of us than we are incomplete versions of whatever our species will look like 200,000 years from now. We are merely different from one another.” 8 Moreover, recent (and not so recent) discoveries have shown that material cultures and behaviors previously solely associated with modern humans seem to have been present in some Neandertal populations 13,18–24 . These data suggest that previous hypothesis that separated the populations into “modern” vs “archaic” no longer work.…”
Section: Introductionmentioning
confidence: 96%
“…The ethnographic record further demonstrates the existence of additional non-utilitarian considerations in the selection of specific stone-types for distinct production trajectories (e.g., Gould and Saggers, 1985;Mcbryde, 1986;Brumm, 2010;Arthur, 2018;Reimer, 2018), stressing the complexity in straight-forwardly inferring lithic-related decision-making during prehistory. Such considerations have been suggested to be relevant in Paleolithic contexts as well (e.g., Moncel et al, 2012;Radovčić et al, 2016;Assaf, 2018;Efrati et al, 2019;Assaf and Romagnoli, 2021;Efrati, 2021;Peresani et al, 2021). The inhabitants of Jaljulia might also have had preferences related to specific visual attributes of the flint types and/or meaning attached to such things as the place of origin of the flint, giving it some significance in their relationships with the landscape around them.…”
Section: Selectivity In Flint Usementioning
confidence: 99%
“…In addition, new archeological evidence has highlighted the behavioral "complexity" of the Middle Paleolithic Neandertals, contributing to a change of perspective with respect to their cognitive abilities. This evidence includes indications that the European Neandertals buried their dead (e.g., Maureille and Van Peer, 1998;Rendu et al, 2013;Maureille et al, 2016), made bone tools (Soressi et al, 2013;Tartar and Costamagno, 2016), used pigments (e.g., Soressi and d'Errico, 2007), collected marine shells (Zilhão et al, 2010) and stones for aesthetic purposes (e.g., Radovčić et al, 2016) and engraved and painted abstract signs in caves (Rodríguez-Vidal et al, 2014;Hoffmann et al, 2018), all independently from modern human influence.…”
Section: Introductionmentioning
confidence: 99%